2019
DOI: 10.3390/ijerph16040638
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Exposure and Poor Nutritional Status Reduce Response to Six Expanded Program on Immunization Vaccines in Children: An Observational Cohort Study of Communities Affected by Gold Mining in the Peruvian Amazon

Abstract: Background: Poor nutritional status combined with mercury exposure can generate adverse child health outcomes. Diet is a mediator of mercury exposure and evidence suggests that nutritional status modifies aspects of mercury toxicity. However, health impacts beyond the nervous system are poorly understood. This study evaluates antibody responses to six vaccines from the expanded program on immunization (EPI), including hepatitis B, Haemophilus influenzae type B, measles, pertussis, tetanus, and diphtheria in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 62 publications
(80 reference statements)
0
10
0
5
Order By: Relevance
“…2020; 86(1): 98, 1-10. DOI: https://doi.org/10.5334/aogh.2896 data collected by this research team, which found high anemia prevalence in children under 12 and disproportionately higher in native communities compared to nonnative communities [9][10].…”
Section: Introductionmentioning
confidence: 88%
“…2020; 86(1): 98, 1-10. DOI: https://doi.org/10.5334/aogh.2896 data collected by this research team, which found high anemia prevalence in children under 12 and disproportionately higher in native communities compared to nonnative communities [9][10].…”
Section: Introductionmentioning
confidence: 88%
“…An optimal nutritional status can affect not only the outcome of an infection but also vaccination efficacy. Indeed, malnutrition might produce a lower antibody response to vaccination in children [ 137 , 138 , 139 , 140 , 141 ]. On the other hand, chronic overfeeding can cause obesity, which, as mentioned above, can lead to an impaired response to vaccination [ 142 , 143 ].…”
Section: Dietmentioning
confidence: 99%
“…Besides chemical pollutants, blood, and urine samples were also analysed for other physiological parameters, such as blood lactate and cyanide [73,74], haematological parameters, and other blood chemistry [47,75], mitochondrial DNA, and other DNA mutations [48,[76][77][78], immunological response to vaccines, and other immune-related proteins [50,79,80], renal and respiratory parameters [75,81], and infectious diseases, such as malaria [82] and HIV [47,83]. Saliva (cortisol salivary) [84], Buccal cells (DNA damage and mutations) [63,77], and stool samples (soil-transmitted helminths and Vibrio cholerae) [85,86] were also reported.…”
Section: Human Samples and Related Biomarkersmentioning
confidence: 99%